Newmark’s Translation Techniques and Degree Semantic Equivalence of Figurative Language in Five Feet Apart novel - Yatimul Chotimah; Januarius Mujiyanto; Rudi Hartono (English Education Journal, 2022)
There are many English novels translated into Indonesian. One of them is Five Feet Apart. The novel not only amazes readers by using the story of a couple with cystic fibrosis but the language in the novel is also presented using figurative language. Sometimes, English novel is still difficult for Indonesian to understand, so it becomes the reason why translation technique is important. This research aims to explain Newmark’s translation technique and to explain the achievement of full, partial, and no equivalence. This research is included in the type of qualitative descriptive research. To obtain data, the researchers collected the words, phrases, clauses, and sentences containing figurative language. Perrine’s classification of figurative language (1997), Newmark’s classification of translation technique (1988), and Bell’s classification of degree semantic equivalence (1997) were used in the analysis of the texts. The analysis was done by identifying, classifying, interpreting, and analyzing the data. The research finding reveals 8 translation techniques used in 202 data. They are couplet, literal translation, modulation, paraphrase, transposition, expansion, cultural equivalence, and compensation. The dominant technique is couplet because the author makes various conditions so it is not enough to translate with only 1 technique. The dominant degree of semantic equivalence is fully equivalence. In conclusion, the large number of fully equivalence indicates that the translator keeps maintaining the meaning and minimizing non-equivalence